Energy system model design and development for thermal hydrolysis process integrated with anaerobic digestion in municipal wastewater treatment plants - Reza Fattahi; Ahmad Hajinezhad; Younes Noorollahi (Results in Engineering)
Anaerobic digestion is commonly employed for sludge stabilization in municipal wastewater treatment plants; however, its efficiency is hindered by the slow rate of sludge biodegradation. To overcome this limitation, pretreatment methods such as the Thermal Hydrolysis Process (THP) are applied to enhance the degradation of sludge prior to anaerobic digestion. Despite significant technological advancements, the major unresolved challenge of the THP method remains its substantial energy consumption. In this study, an integrated energy system model combining thermal hydrolysis with anaerobic digestion was developed and analyzed using detailed process calculations and energy system modeling. Results from the case study indicate that integrating THP with anaerobic digestion reduces anaerobic digester tank volumes by approximately 80 %, improves organic matter degradation efficiency by 14 %, increases biogas energy production by 15 %, and enhances sludge dewatering efficiency by at least 20 %. Nonetheless, the high energy requirement for steam generation in the THP results in a negative overall energy balance, despite a 32 % increase in the energy content of produced biogas. This study highlights critical areas for further optimization in integrated thermal hydrolysis and anaerobic digestion systems.